Pseudomonas extremaustralis sp. nov. a polyhydroxybutyrate-producer isolated from Antarctic environments - López, Nancy Irene; Pettinari, María Julia; Stackebrandt, Erko; Tribelli, Paula Maria; Põtter, Markus; Steinbüchel, Alexander; Mendez, Beatriz Silvia (Current Microbiology)
A Gram-negative, mobile, rod-shaped, non-spore-forming bacterium (strain 14-3T) was isolated from a temporary pond in Antarctica. On the basis of 16S rRNA gene sequence similarity, strain 14-3T was shown to belong to the genus Pseudomonas sensu stricto. Physiological and biochemical tests supported the phylogenetic affiliation. Strain 14-3T is closely related to Pseudomonas veronii DSM 11331T, sharing 99.7% sequence similarity. DNA–DNA hybridization experiments between the two strains showed only moderate reassociation similarity (35.1%). Tests for arginine dihydrolase and nitrate reduction were positive, while those for denitrification, indol production, glucose acidification, urease, ß-galactosidase, esculin, caseine and gelatin hydrolysis were negative. Growth of this bacterium occurred in a range from 4 to 37°C but not at 42°C. It accumulated poly(3-hydroxybutyrate) when grown on sodium octanoate medium. Strain 14-3T therefore represents the type strain of a new species, for which the name Pseudomonas extremaustralis sp. nov. is proposed. The type strain 14-3T has been deposited as DSM 17835T and as CIP 109839T. Fil: López, Nancy Irene. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina Fil: Pettinari, María Julia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina Fil: Stackebrandt, Erko. Deutsche Sammlung von Mikroorganismen und Zellkulturen; Alemania Fil: Tribelli, Paula Maria. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina Fil: Põtter, Markus. Universität Münster; Alemania Fil: Steinbüchel, Alexander. Universität Münster; Alemania Fil: Mendez, Beatriz Silvia. Consejo Nacional de ...